2022
DOI: 10.1112/blms.12561
|View full text |Cite
|
Sign up to set email alerts
|

On the smoothed analysis of the smallest singular value with discrete noise

Abstract: Let A$A$ be an n×n$n\times n$ real matrix, and let M$M$ be an n×n$n\times n$ random matrix whose entries are independent and identically distributed sub‐Gaussian random variables with mean 0 and variance 1. We make two contributions to the study of sn(A+M)$s_n(A+M)$, the smallest singular value of A+M$A+M$. (1)We show that for all ε⩾0$\epsilon \geqslant 0$, double-struckP[snfalse(A+Mfalse)⩽ε]=O(εn)+2e−normalΩfalse(nfalse),\begin{equation*} \mathbb {P}[s_n(A + M) \leqslant \epsilon ] = O(\epsilon \sqrt {n}) +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In [40], it is shown that the above small ball probability bound can be significantly improved to match the average-case result of Rudelson and Vershynin [70], under the assumption that a positive fraction of the singular values of M are of order O( √ n). More specifically, for every c ∈ (0, 1) and C > 0, and any fixed matrix M with s n−⌊cn⌋ (M ) ≤ C√ n, one has…”
Section: Quantitative Invertibility In Matrix Computationsmentioning
confidence: 84%
See 2 more Smart Citations
“…In [40], it is shown that the above small ball probability bound can be significantly improved to match the average-case result of Rudelson and Vershynin [70], under the assumption that a positive fraction of the singular values of M are of order O( √ n). More specifically, for every c ∈ (0, 1) and C > 0, and any fixed matrix M with s n−⌊cn⌋ (M ) ≤ C√ n, one has…”
Section: Quantitative Invertibility In Matrix Computationsmentioning
confidence: 84%
“…On the other hand, it was observed that for certain discrete random matrices, such as random sign (Bernoulli) matrices, no shift-independent small ball probability bounds for s min (A + M ) are possible [87,90,40]. In particular, it is shown in [40] that, assuming A has i.i.d entries taking values ±1 with probability 1/4 and zero with probability 1/2, every L ≥ 1, and every positive integer K, sup…”
Section: Quantitative Invertibility In Matrix Computationsmentioning
confidence: 99%
See 1 more Smart Citation